Radiological scales predicting delayed cerebral ischemia in subarachnoid hemorrhage: systematic review and meta-analysis - Wessel E. van der Steen; Eva L. Leemans; René van den Berg; Yvo B.W.E.M. Roos; Henk A. Marquering; Dagmar Verbaan; Charles B.L.M. Majoie (2019)
Delayed cerebral ischemia (DCI) is a severe complication of aneurysmal subarachnoid hemorrhage (aSAH). The extent of subarachnoid blood is a strong predictor of DCI and is frequently estimated with the Fisher scale, modified Fisher scale, or Hijdra sum score. It is unclear which scale has the strongest association with clinical DCI. To evaluate this, we performed a systematic review of the literature. We performed a MEDLINE and EMBASE search from 1980 to 20th of June 2017. Radiological grade and occurrence of clinical DCI were extracted along with odds ratios (ORs) for DCI. When possible, pooled ORs with 95% confidence intervals were calculated per grade increase on the radiological scale. Fifty-three studies were included. The Fisher scale was significantly associated with DCI in 62% of the studies compared to 88–100% for the other scales. In studies using the Fisher scale, Fisher 3 had the strongest association with DCI (pooled OR 3.21 (1.87–5.49)). In studies using the modified Fisher score, DCI occurred most frequently (42%) in modified Fisher 4. No pooled OR could be calculated for the other scales. The Fisher scale, modified Fisher scale, and Hijdra sum score are all associated with clinical DCI. The risk of DCI, however, does not increase with increasing Fisher grade as opposed to the modified Fisher scale. Furthermore, the modified Fisher scale was more commonly significantly associated with DCI than the Fisher scale, which may advocate using the modified Fisher in future SAH-related studies.